The efficacy of diffusion weighted imaging for detection of acute pancreatitis and comparison of subgroups according to Balthazar classification - Yencilek, Esin; Telli, Seçil; Tekesin, Kemal; Özgür, Anıl; Çakır, Özcan; Türkoğlu, Özlem; Meriç, Kaan; Şimşek, Masum (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The aim of this study was to measure the apparent diffusion coefficient (ADC) values detected by diffusion-weighted imaging (DWI) in acute pancreatitis and compare them with computerized tomography (CT) findings in acute pancreatitis subgrouped by the Balthazar classification. Materials and Methods: The study population included 50 patients diagnosed with clinical pancreatitis who were evaluated with both multidetector CT and magnetic resonance imaging (MRI) within 24 h of clinical presentation. We calculated pancreatic ADC values obtained from DWI (b=0 and b=1000 mm2/sn). These values were compared with their normal counterparts (n=24). The patients with acute pancreatitis were subgrouped according to the Balthazar classification. The mean ADC values were calculated in each subgroup, and they were compared with control ADC values. Results: The mean pancreatic ADC values in acute pancreatitis (1.19×10−3 mm2/sn ±0.32) was significantly lower than in the normal group (1.78×10−3 mm2/sn ±0.29) (p<0.001). In the subgroup analysis, ADC values in each group were significantly lower than in the control group (p<0.001). In addition, as severity of pancreatitis increased according to the Balthazar classification, lower ADC values were noted. Conclusion: DWI with MRI and ADC values are helpful in the diagnosis of all subgroups of acute pancreatitis. Due to the lack of CT findings in grade A patients, DWI may be helpful in the diagnosis in this group as well.